Unmasking the Perils of Festive Fasting: A Clinical and Legal Insight into Buckwheat Poisoning During Janmashtami (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
During the Hindu festival of Janmashtami, many people fast and consume buckwheatflour (kuttu ka atta) as a gluten-free substitute. However, incidents of buckwheatpoisoning have surfaced, raising concerns regarding its safety during fasting. Thisstudy aimed to investigate the clinical and epidemiological characteristics, identifypredictors of severity, evaluate biochemical markers, and examine the medicolegalimplications of buckwheat poisoning associated with Janmashtami fasting.A retrospective review was conducted of 110 patients admitted with suspectedbuckwheat poisoning at a tertiary care teaching hospital. Data on demographics,clinical symptoms, severity factors, and biochemical parameters were collected,followed by analysis. The study also explored medicolegal dimensions to understandthe broader impact of these poisoning cases.The findings revealed that most patients were adult males from lower socioeconomicgroups. The most common symptoms observed were gastrointestinal issues,respiratory problems, and neurological disturbances. Factors predicting the severityof poisoning were identified, including the amount of buckwheat consumed, existinghealth conditions, and delays in seeking medical care. Biochemical analysis revealedelevated levels of markers corresponding to the severity of symptoms. Medicolegalanalysis pointed to shortcomings in food safety regulations, labelling, and publicawareness, suggesting potential legal liabilities for food vendors and producers.Buckwheat poisoning during Janmashtami fasting presents a notable health risk,necessitating public health measures and stricter food safety standards. Healthcareproviders should be particularly alert during fasting periods, and public awarenesscampaigns are essential to prevent future cases. Medicolegal considerations highlightthe need for robust food safety legislation and improved consumer education tosafeguard the public health.
Keywords: Buckwheat poisoning; Janmashtami fasting; Clinical epidemiology; Severity predictors; Biochemical markers; Medicolegal implications; Food safety